The Protection of Domestic Violence Victims in the Present Context. Enforcement of the Protection Order - Maria-Magdalena Barsan (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law, 2024)
This article approaches issues pertaining to the protection of domestic violence victims by emphasizing the lawmaker’s initiative to expand the enforcement of the protection order by Law no 26/2024. Enforcement of the protection order to protect all victims regardless of the relation between the victim and the assailant and the form of violence (physical or psychological) is an element of legislative novelty. The subject of this endeavour will be the rights of the victims of crimes which entail acts of violence, by describing both national law and international law.